Analysis of the Influencing Factor on Steady-state Temperature Field of Axlebox Bearing for High Speed Train - Jiang Jiulin Xu Honghai Jiang Xingjia Ke Mengfu (Jixie chuandong)
Aiming at the temperature warning problem of axlebox bearing in a high-speed train in China, ANSYS is used to establish the finite element simulation model of axlebox bearing, the frictional heating power of the bearing is distributed according to the force of each rolling element, the steady temperature field analysis of the axlebox bearing is completed by using FLUEEN and the validity of the model is verified by using the actual monitoring data. On this basis, the influence of wind direction and grease injection amount on the temperature field of axlebox bearings is analyzed, and the influence of wind speed, driving speed and ambient temperature on temperature field is simulated by orthogonal test method. The results show that the wind direction has little effect on the temperature field of the axlebox bearing, when the grease injection amount is 240 g,the temperature of the temperature measurement hole and the maximum temperature of the bearing are higher than 220 g. The wind speed, driving speed and ambient temperature have significant influence on the temperature of the temperature measurement hole, and the degree of influence from the largest to the smallest is the driving speed, ambient temperature, wind speed. The temperature of the temperature measuring hole and maximum temperature of the bearing decrease with the increase of the wind speed, and increase with the increase of the driving speed and ambient temperature, however, the wind speed and ambient temperature have little effect on the maximum bearing temperature. The research results provide a reference for the analysis of the cause of the temperature warning of the axle box bearing and the reasonable setting of the reasonable setting of the warning threshold of the temperature sensor.